Optimalisasi Strategi Manajemen Berbasis Data Untuk Peningkatan Kualitas Pengajaran Sekolah Dasar - Faiz Rahmawati (Genius: Jurnal Ekonomi Dan Manajemen, 2024)
This study aims to examine the optimisation of data-driven management strategies in improving teaching quality in primary schools. In an educational context that is increasingly dependent on technology, the use of data to support educational decisions is crucial. This research adopts a qualitative approach using data triangulation techniques to ensure the validity of the findings. Data were obtained from in-depth interviews with principals, teachers and administrative staff in several primary schools, as well as direct observation of the data-driven learning process. The main objective of this study is to understand how data-driven management strategies can be implemented in primary schools and analyse the factors that influence the effectiveness of its use in improving teaching quality. The results show that although the implementation of data-driven management has positive impacts, such as improved lesson planning and better communication with parents, the main challenge lies in the limited technological infrastructure and the lack of training for teachers in data management. The research also confirms that the successful use of data is highly dependent on the quality of training provided to teachers and the provision of adequate infrastructure. Overall, this study suggests the need for strengthening technical capacity and policies that support data management in primary schools to achieve optimisation of the use of data-based management in improving teaching quality.